KEDUDUKAN CRYPTOCURRENCY SEBAGAI INVESTASI DALAM EKONOMI ISLAM - Angga Syahputra; Khalish Khairina (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2022)
One of the investments that people are interested in today is Cryptocurrency. This is a form of investment that occurs due to advances in the world of technology that are felt by the community without exception also for Muslims. Conventional investment is defined as having broad benefits and impacts on the country's economy. However, Islam provides various limits in investing. For an investment to be recognized in Islam, four aspects must be owned, namely: material/financial aspects, halal aspects, social and environmental aspects, and divine aspects. For this reason, this research will describe in detail, whether cryptocurrencies meet these aspects or not. In answering these problems, the researcher used a descriptive qualitative approach with valid secondary data sources. This research results that none of the four aspects can be fulfilled from cryptocurrency, both material/financial aspects, halal aspects, social and environmental aspects as well as divine aspects.Keywords: Cryptocurrency; investment; Islamic economy